2015
DOI: 10.1080/15384047.2015.1108494
|View full text |Cite
|
Sign up to set email alerts
|

Absence of germlineCDKN2Amutation in Sicilian patients with familial malignant melanoma: Could it be a population-specific genetic signature?

Abstract: Germline CDKN2A mutations have been described in 25% to 40% of melanoma families from several countries. Sicilian population is genetically different from the people of Europe and Northern Italy because of its historical background, therefore familial melanoma could be due to genes different from high-penetrance CDKN2A gene. Four hundred patients with cutaneous melanoma were observed in a 6-years period at the Plastic Surgery Unit of the University of Palermo. Forty-eight patients have met the criteria of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 67 publications
0
15
1
Order By: Relevance
“…R24P has also been reported in other European populations, mainly British (14, 33), but shows a higher frequency in our Greek familial cases. In our familial cases we identified 2 distinct p.G101 mutations, p.G101R and p.G101E, whereas all other studies report a W protein change at the same position (1, 15, 34). Overall, these changes pinpoint that this position could be a hotspot for mutagenesis.…”
Section: Discussioncontrasting
confidence: 54%
“…R24P has also been reported in other European populations, mainly British (14, 33), but shows a higher frequency in our Greek familial cases. In our familial cases we identified 2 distinct p.G101 mutations, p.G101R and p.G101E, whereas all other studies report a W protein change at the same position (1, 15, 34). Overall, these changes pinpoint that this position could be a hotspot for mutagenesis.…”
Section: Discussioncontrasting
confidence: 54%
“…Nevertheless, studies in South-Italian populations reported discrepant results. Di Lorenzo et al screened a total of 48 familial CMM Sicilian patients for germline mutations in CDKN2A and CDK4 genes; they found that none of the examined families carried mutations in exon 2 of CDK4 and only one patient harboured a rare missense mutation in exon 2 of CDKN2A (2.1%) [33]. Another study was performed in Sardinia island including 24 family cases of CMM; again, only one (4.2%) CDKN2A mutation was detected [1].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility to cutaneous melanoma has been investigated in Italian high-risk melanoma patients from different geographical regions. CDKN2A 6,[20][21][22][23][24][25][26][27][28][29][30] , CDK4 6,21,22,27,28,30 , and MC1R 6,24,25,28,31,32 genes have been screened in almost all published studies, MITF in only one study 19 , and POT1 in the discovery manuscript 11 ; no studies have analyzed the promoter of the TERT gene. In the present study, we carried out a mutational analysis of the major known melanoma susceptibility genes (CDKN2A, CDK4 exon 2, POT1 p.S270N, MC1R, MITF exon 10, and the TERT promoter) in high-risk FM and spMPM patients from Central Italy and evaluated the association of mutational status with the clinicopathological characteristics of patients and tumors.…”
Section: Introductionmentioning
confidence: 99%